2020
DOI: 10.1016/j.bpj.2020.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Simulations Provide Insight into the Molecular Mechanism Underlying Dynamic Instability

Abstract: The dynamic instability of microtubules (MTs), which refers to their ability to switch between polymerization and depolymerization states, is crucial for their function. It has been proposed that the growing MT ends are protected by a ''GTP cap'' that consists of GTP-bound tubulin dimers. When the speed of GTP hydrolysis is faster than dimer recruitment, the loss of this GTP cap will lead the MT to undergo rapid disassembly. However, the underlying atomistic mechanistic details of the dynamic instability remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…S5), and found that a COM reaction coordinate can best mesh together the MD to BD scales. Additionally, it will be important in the future for our thermokinetic model to include minus end dynamics as another way to validate our modeling results as well as long-range effect of neighbors 38 (without ad hoc parametrization) and the seam interactions 64 to investigate their potential effects on the interaction energies.…”
Section: Discussionmentioning
confidence: 99%
“…S5), and found that a COM reaction coordinate can best mesh together the MD to BD scales. Additionally, it will be important in the future for our thermokinetic model to include minus end dynamics as another way to validate our modeling results as well as long-range effect of neighbors 38 (without ad hoc parametrization) and the seam interactions 64 to investigate their potential effects on the interaction energies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the holistic or bond model [23,27] assumes that MT catastrophe can be explained by a sequential weakening of lateral inter-dimer contacts accompanied by a simultaneous strengthening of longitudinal contacts. Also here, recent atomistic simulations of full MT lattices suggest that lateral interactions in GDP-MTs might be weaker than those in GTP-MTs [25]. Finally, the most recent 'no expansion' model [24] provides an alternative view of the cap maturation process in which both pure GTP-and pure GDP-MTs have equally compacted lattices, while the higher-energy expanded lattice induced by GTP hydrolysis (mimicked by GMPCPP) corresponds to an intermediate, phosphate-releasing state.…”
Section: Introductionmentioning
confidence: 70%
“…In this model, lattice rupture is initiated at the seam because of the greater distance, and presumably weaker interactions, between PFs at this interface observed in unsymmetrized cryo-EM reconstructions. The role of the MT seam as the weakest interface is supported by recent computational evidence [25], but has been challenged experimentally [26]. In contrast, the holistic or bond model [23,27] assumes that MT catastrophe can be explained by a sequential weakening of lateral inter-dimer contacts accompanied by a simultaneous strengthening of longitudinal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical modeling of microtubules ( Kasas et al, 2004a ; Kasas et al, 2004b ; Molodtsov et al, 2005 ; VanBuren et al, 2005 ; Schaap et al, 2006 ; Deriu et al, 2007 ; Heuvel et al, 2007 ; Deriu et al, 2008 ; Dima and Joshi, 2008 ; Deriu et al, 2010 ; Sept and MacKintosh, 2010 ; Wells and Aksimentiev, 2010 ; Grafmuller and Voth, 2011 ; Ji and Feng, 2011a ; b ; Peter and Mofrad, 2012 ; Grafmuller et al, 2013 ; Theisen et al, 2013 ; Kononova et al, 2014 ; Lazarus et al, 2015 ; Soheilypour et al, 2015 ; Havelka et al, 2017 ; Stevens, 2017 ; Szatkowski et al, 2019 ; Tong and Voth, 2020 ) faces a huge challenge due to the micrometer length. All-atom molecular dynamics (MD) simulations have been primarily used to investigate the atomistic details of the interactions between the α- and β-tubulins ( Deriu et al, 2007 ; Deriu et al, 2008 ; Sept and MacKintosh, 2010 ; Wells and Aksimentiev, 2010 ; Grafmuller and Voth, 2011 ; Grafmuller et al, 2013 ; Havelka et al, 2017 ) for short microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…All-atom molecular dynamics (MD) simulations have been primarily used to investigate the atomistic details of the interactions between the α- and β-tubulins ( Deriu et al, 2007 ; Deriu et al, 2008 ; Sept and MacKintosh, 2010 ; Wells and Aksimentiev, 2010 ; Grafmuller and Voth, 2011 ; Grafmuller et al, 2013 ; Havelka et al, 2017 ) for short microtubules. Recent all-atom simulations ( Tong and Voth, 2020 ) reached a length scale of a 1 μm microtubule including 3 protofilaments. Additionally, coarse-grained (CG) models ( Dima and Joshi, 2008 ; Deriu et al, 2010 ; Ji and Feng, 2011a ; Ji and Feng, 2011b ; Theisen et al, 2013 ; Kononova et al, 2014 ; Lazarus et al, 2015 ; Soheilypour et al, 2015 ; Stevens, 2017 ; Szatkowski et al, 2019 ) have also been used to model longer microtubules.…”
Section: Introductionmentioning
confidence: 99%